REALIZATION OF FINITE ELEMENT METHOD USING ALTERNATIVE MODELS - Камаєва, Світлана Олегівна; Федоришин, Максим Григорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This work is devoted to the solving task about torsion of prism rod with the rectangular section. The opportunity to apply the finite element method using not only standard models, but also alternative, built by the geometric modeling, is examined. The accuracy of estimation depending on the order and quantity of elements, that cover the transverse section is analyzed. The inverse task with the aim to obtain optimized models is being solved.